FAKTOR-FAKTOR YANG MEMENGARUHI MANAJEMEN LABA PADA PERUSAHAAN NON-KEUANGAN DI BURSA EFEK INDONESIA - UMAR ISSA ZUBAIDI; KURNIA JOSUA SILABAN (E-Jurnal Akuntansi TSM, 2021)
This research aims to obtain empirical evidence about leverage, firm size, managerial ownership, institutional ownership, growth, fixed asset turnover, and profitability toward earnings management. This research uses sample of 222 data from 74 non-financial sector companies which listed in Indonesia Stock Exchange during 2017-2019. This research used purposive sampling method as sample selection. Method used in this research is multiple regression analysis method. The result shows that profitability has influence to earnings management. While, leverage, firm size, managerial ownership, institutional ownership, growth, and fixed asset turnover do not have significant influence to earnings management